The Platonizing Sethian background of Plotinus's mysticism - Mazur, Zeke (Nag Hammadi and Manichaean studies, 2021)
Introduction: The gnostic background of Plotinus's mysticism -- The structure of Plotinus' ascent to mystical union with the One -- The identity of prenoetic and hypernoetic subjects in Plotinus -- "The way of ascent is the way of descent" : the mechanism of transcendental apprehension in Platonizing Sethian Gnosticism -- Conclusion: Dissolving boundaries.